Horace, Odes 4.1: a Contradiction Removed*. (19th January 2017) - Kovacs, David
Abstract: Odes 4.1 is difficult to understand on a literal level. At its beginning Horace is complaining that Venus, after leaving him alone for many years, is attacking him, that is, he is feeling a reawakening of sexual desire. But after suggesting that the goddess go off to visit Paullus Fabius Maximus and describing the rewards the young man will give her, he returns to himself. Now, he says, he is delighted by neither woman nor boy nor by the prospect of mutuality in love, that is, he is not in the grip of eros . Additionally, the use of iuuare, 'delight', with a person as subject seems to be without any parallel. These problems disappear if in l. 29 we read mi for me : 'I no longer have either woman or boy (as lover) nor do I have the hope of mutual affection.' Horace's having no lover and no hope of one is compatible with his feeling a generalized desire for sex or a desire for someone unattainable. The tone of the last two quatrains is affected as well as the contribution of the poem to the fourth book of odes.